Atlas of Religion in China: Social and Geographical Contexts - Yang, Fenggang (Brill, 2018)
This atlas maps religious sites and describes social and demographic characteristics of religious believers in contemporary China.; Readership: All people interested in religion in China; academic libraries; research institutes on China